ANALISIS PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL, MANAJEMEN LABA, KARAKTERISTIK PERUSAHAAN, KANTOR AKUNTAN PUBLIK, GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM INDEKS LQ-45 DI BURSA EFEK INDONESIA - Dinda, Bahiira Albasitha Permata; Hwihanus, Hwihanus (LP2M Universitas Bina Bangsa, 2024)
This study aims to find out how much influence financial performance, capital structure, profit management, company characteristics, public accounting firms, and good corporate governance on tax avoidance. This research is a quantitative research using secondary data obtained from the annual financial statements available on the official website of the Indonesia Stock Exchange (IDX). The population of this study is 21 manufacturing companies listed on the LQ-45 Index on the Indonesia Stock Exchange from 2020-2022. The sampling technique of this study uses a purposive sampling technique, so that as many as 13 companies were obtained. The data was processed using the SmartPLS program application. The results of this study show that the results of hypothesis testing have a significant positive effect on financial performance on capital structure, profit management on tax avoidance, capital structure on profit management, public accounting firms on good corporate governance, and public accounting firms on tax avoidance. The results of hypothesis testing that resulted in a significant negative effect were financial performance on tax avoidance, profit management on characteristics, characteristics on public accounting firms, characteristics on tax avoidance, good corporate governance on tax avoidance. Meanwhile, the results of hypothesis testing that produced a not significant positive effect was the capital structure on tax avoidance